2014
DOI: 10.1038/npp.2014.124
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Amphetamine Action is Contingent on αCaMKII

Abstract: Addiction to psychostimulants (ie, amphetamines and cocaine) imposes a major socioeconomic burden. Prevention and treatment represent unmet medical needs, which may be addressed, if the mechanisms underlying psychostimulant action are understood. Cocaine acts as a blocker at the transporters for dopamine (DAT), serotonin (SERT), and norepinephrine (NET), but amphetamines are substrates that do not only block the uptake of monoamines but also induce substrate efflux by promoting reverse transport. Reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 48 publications
4
48
0
Order By: Relevance
“…Deletion of Maged1 in the striatum did not induce any alteration in the behaviours examined. Such a decoupling between locomotor sensitization and CPP has been reported for other knockout models, such as mice lacking calcium/ calmodulin protein kinase IIa, a protein involved in synaptic plasticity [48], suggesting that these behavioural responses to cocaine are driven by different mechanisms. Interestingly, the complete lack of Maged1 impaired motor coordination but did not affect motor learning, whereas deletion of Maged1 only in the PFC resulted in no alteration of motor coordination, but in a severe deficit in motor learning.…”
Section: Discussionsupporting
confidence: 56%
“…Deletion of Maged1 in the striatum did not induce any alteration in the behaviours examined. Such a decoupling between locomotor sensitization and CPP has been reported for other knockout models, such as mice lacking calcium/ calmodulin protein kinase IIa, a protein involved in synaptic plasticity [48], suggesting that these behavioural responses to cocaine are driven by different mechanisms. Interestingly, the complete lack of Maged1 impaired motor coordination but did not affect motor learning, whereas deletion of Maged1 only in the PFC resulted in no alteration of motor coordination, but in a severe deficit in motor learning.…”
Section: Discussionsupporting
confidence: 56%
“…It is possible that although cocaine binding to DAT may be necessary to initiate cocaine reward subsequent alterations in DA signals may lead to modulation of other neuronal substrates including NET regulation, which in collaboration may evoke cocaine-associated behaviors. In addition, it is now clear that multiple DA brain regions are implicated in producing different aspects of cocaine reward, which may be attributed by the differences in DAT expression levels in different brain regions (78,79). NET expression is localized to noradrenergic terminals where it facilitates transport of NE and DA (80,81).…”
Section: Discussionmentioning
confidence: 99%
“…Fog et al (2006) also found that intracellular perfusion of activated CaMKIIa enhanced AMPH-induced DA efflux. Most recently, Steinkellner et al (2014) reported a reduction in AMPH-evoked DA release in vivo via microdialysis in CaMKIIa knockout mice as well as a blunting of AMPHinduced locomotor activation. Consistent with these findings, transgenic expression of a CaMKII inhibitory peptide blocks the locomotor stimulating actions of AMPH in Drosophila melanogaster (Pizzo et al, 2014).…”
Section: A Regulation Of Dopamine Transporter Bymentioning
confidence: 99%